Insights into the differential fragmentation processes in rock avalanche emplacement from field investigation and experimental study - Wang, Yu-Feng; Cheng, Qian-Gong; Lin, Qi-Wen; Li, Kun; Ji, Yan-Dong (Frontiers in Earth Science, 2022)
Fragmentation is a universal phenomenon associated with rock avalanches, resulting in an abundance of complex sedimentological structures. If studied in detail, these structures can provide insights into rock avalanche emplacement processes. Here, six typical avalanche cases are carefully analyzed in conjunction with an analogue experiment. Findings reveal the carapace facies is characterized by clast-supported structures composed of large blocks with sedimentological structures that include retained stratigraphic sequences, imbricate structures, and jigsaw structures. The body facies presents a high degree of fragmentation, with block-rich zones, fine matrix-rich zones, jigsaw structures, and inner shear zones. The basal facies displays the highest degree of fragmentation, however, it is mainly composed of millimeter grains with thin shear strips. Consistent with the field investigations, differential fragmentation is also observed in the analogue tests, with the vertical dimension of the carapace facies mainly fragmented along the lines of pre-existing structures; the body facies fragmented with an abundance of new fractures; and the basal facies fragmented into fine grains. Meanwhile, layer sequences preserved in longitudinal and vertical profiles are also observed in the analogue tests, indicating a low disturbance in the propagation. We, therefore, propose that a process characterized by a sparse state, dominated by collisions, minor disturbance, and pervasive dynamic fragmentation likely occurs in the carapace facies, with fragmentation mainly controlled by the breakage of pre-existing, fully-persistent structures. The body facies is mainly controlled by the fracturing of the weak, less-persistent structures, and the basal facies displays the highest degree of fragmentation with an abundance of new fractures. In the entire propagation, the avalanche mass displays low-disturbance laminar flow.